2014
DOI: 10.1080/15427528.2013.858283
|View full text |Cite
|
Sign up to set email alerts
|

Planting Date Effect on Yield of Tomato, Eggplant, Pepper, Zinnia, and Snapdragon in High Tunnel in Mississippi

Abstract: High tunnels' are unheated greenhouse structures used to extend the growing season and protect high-value horticultural crops. High tunnels have been used for many years worldwide and their popularity has increased in Mississippi recently. A planting date study of 'Roma' tomato ( Solanum lycopersicum L.), 'Legend' tomato, 'Ichiban' eggplant ( Solanum melongena L.), 'Sweet Banana' pepper ( Capsicum annuum L.), 'Benary's Giant' zinnia ( Zinnia elegans L.), and 'Potomac Red' snapdragon ( Antirrhinum majus L.) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
(15 reference statements)
0
13
0
1
Order By: Relevance
“…In Mississippi, earlier plantings provided earlier harvests without yield loss [59]. However, there was no planting date effect on the total marketable yield for tomatoes, eggplants or banana peppers.…”
Section: Tomatoesmentioning
confidence: 94%
“…In Mississippi, earlier plantings provided earlier harvests without yield loss [59]. However, there was no planting date effect on the total marketable yield for tomatoes, eggplants or banana peppers.…”
Section: Tomatoesmentioning
confidence: 94%
“…Studies have shown that air temperature inside the tunnel is 3 to 20 °C higher and that soil temperature is 2-5 °C higher than soil temperatures recorded in open fields (Ogden and van Iersel, 2009;Zhao et al, 2014). Studies conducted in tomatoes and strawberries indicate that the increase in temperature in high tunnels directly influences fruit precocity, with a harvest starting between 7 and 21 d earlier than in the open field (Wien, 2009;Singh et al, 2012;Cowan et al, 2014;Zhao et al, 2014). An increase in temperature of 2-3 °C and in relative humidity of 2-6% has been reported in strawberries grown under tunnels (Singh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, little information exists on the physiological and productive changes in woody plants, such as blueberries (Demchak, 2009). Studies have shown that air temperature inside the tunnel is 3 to 20 °C higher and that soil temperature is 2-5 °C higher than soil temperatures recorded in open fields (Ogden and van Iersel, 2009;Zhao et al, 2014). Studies conducted in tomatoes and strawberries indicate that the increase in temperature in high tunnels directly influences fruit precocity, with a harvest starting between 7 and 21 d earlier than in the open field (Wien, 2009;Singh et al, 2012;Cowan et al, 2014;Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…El uso de túneles, permite ampliar los ciclos de producción, aumentan la calidad y rendimiento de los cultivos, reducir la incidencia de plagas y enfermedades y protección contra condiciones climáticas adversas (Lamont, 2009;Rogers et al, 2012;Zhao et al, 2014).…”
Section: Introductionunclassified
“…The use of tunnels allows to extend production cycles, increases crop quality and yield, reduces pest and disease incidence, and protects against adverse climatic conditions (Lamont, 2009;Rogers et al, 2012;Zhao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%